Clinical and clinicopathological characteristics, treatment, and outcome for dogs and cats with confirmed foxtail foreign body lesions: 791 cases (2009–2018). Issue 5 (6th May 2022) - Philp, Helen S.; Epstein, Steven E.; Hopper, Kate
Abstract: Objective: To describe the clinical and clinicopathological characteristics, treatment, and outcome for dogs and cats with a confirmed foxtail. Design: Retrospective study utilizing a medical records database over a 10‐year period from January 1, 2009 to December 31, 2018. Setting: University teaching hospital. Animals: Seven hundred and fifty‐four dogs and 37 cats with a diagnosis of foxtail foreign body. Cases with direct visualization by a clinician or on histopathology were included. Information extracted for each case included signalment; anatomical foxtail location; clinicopathological and imaging findings; treatments and interventions provided; and outcome. Measurements and Main Results: The prevalence of foxtail associated disease was 0.25% in dogs and 0.07% in cats over this time period. Most animals were young to middle‐aged and presented in the summer months. The most common location in dogs was the aural canal, cutaneous/subcutaneous space, and nasal canal. In cats, ocular foxtails were most common (30/37). Blood work changes were nonspecific. Ultrasound supervised by a boarded radiologist was utilized in 114 cases, mainly for subcutaneous, sublumbar, and intracavitary foxtail locations, with successful location of a foxtail in 72.8% of cases scanned. Computed tomography was performed in 78 dogs with suspected intracavitary foxtail migration, and in all cases, structural changes related to the presence of the foxtail were found. Anerobic bacteria were most commonly isolated when a culture was submitted, with Actinomyces spp. rarely isolated. The most common of the 120 anaerobic isolates were Bacteroides / Prevotella spp. ( n  = 38), Fusobacterium spp. ( n  = 32), and Peptostreptococcus anaerobius ( n  = 30). Conclusions: The short‐term outcome for foxtail‐associated lesions is good, and most cases can be managed on an outpatient basis. A minority of cases develop life‐threatening disease and may require a multidisciplinary approach of multimodal imaging, endoscopy, or surgery.